2016
DOI: 10.1080/13880209.2016.1255976
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, antioxidant and protective effect of cactus cladodes extract against lithium-induced liver injury in rats

Abstract: Context: Opuntia ficus-indica (L.) Mill. (Castaceae) (cactus) is used in Tunisian medicine for the treatment of various diseases. Objective: This study determines phytochemical composition of cactus cladode extract (CCE). It also investigates antioxidant activity and hepatoprotective potential of CCE against lithium carbonate (Li2CO3)-induced liver injury in rats. Materials and methods: Twenty-four Wistar male rats were divided into four groups of six each: a control group given distilled water (0.5 mL/100 g b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 46 publications
(62 reference statements)
3
30
0
Order By: Relevance
“…This finding agrees with Saxena et al [86], who reported that treatment with QU seed powder significantly reduced the activities of CCl4-induced hepatic enzymes in Swiss albino mice (Mus musculus). Moreover, pretreatment with PP extract significantly reduced the levels of serum hepatic enzymes elevated upon lithium exposure in Wistar rats (Rattus norvegicus) [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding agrees with Saxena et al [86], who reported that treatment with QU seed powder significantly reduced the activities of CCl4-induced hepatic enzymes in Swiss albino mice (Mus musculus). Moreover, pretreatment with PP extract significantly reduced the levels of serum hepatic enzymes elevated upon lithium exposure in Wistar rats (Rattus norvegicus) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Zhai and Liu [95] reported that PP increased the antioxidant potential of hepato-pancreas in Nile tilapia. In addition, Ben Saad et al [16] reported that the administration of PP extract had a strong hepatoprotective effect on the oxidative lithiummediated damage in rat models, which could be attributed to the antioxidant activity of the active constituents such as phenolics, flavonoids, and polysaccharides. Avila-Nava et al [96] reported that PP exhibited both in vitro and in vivo antioxidant activities; therefore, its consumption protected the body from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study [ 4 ] we have shown that Opuntia ficus indica extract is rich in natural antioxidants compounds and exhibits an excellent antioxidant activity (Tables 1 and 2 ). Moreover, we have shown that HPLC analysis of CCE revealed the presence of phenolic acids and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Among these synthetic drugs and chemicals, both organic, but mainly inorganic chemicals are widely used, and have some severe adverse effects. 372 376 Use of Malva species for constipation relief is known in most traditional medicines of Asia (M. neglecta 36,41,52,59 , M. parviflora 67 and M. sylvestris 108,110,115 ). This activity is recently investigated by several groups.…”
Section: New Compoundsmentioning
confidence: 99%